Indonesian Capital Market Reaction to Fed Interest Rate Cut in 2024 - Saputri, Risma Andreliani; Santoso, Fahrul Imam (GOVERNORS, 2025)
Capital markets are often influenced by global monetary policy, including changes in the Fed's interest rates. This decline in interest rates can affect investors' expectations of risk and return. This research aims to analyze the capital market reaction to the Fed's interest rate reduction by looking at differences in abnormal returns, trading volume activity, and bid-ask spread. The research objects in this study are energy sector companies listed on the Indonesia Stock Exchange with an estimation period of 100 days before the event and a research period of 11 days, consisting of 5 days before, during and 5 days after the event. This research uses the event study method with a sample of 29 companies selected through purposive sampling. Data analysis techniques include descriptive statistical analysis, Shapiro-Wilk normality test, and Wilcoxon Signed Rank Test hypothesis testing. The research results show that abnormal returns do not experience significant differences before and after the Fed’s interest rate cuts on September 18 and December 18, 2024, indicating that the market had possibly anticipated these monetary policy changes. However, a significant difference on November 7, 2024, suggests that the announcement on this date may have contained unexpected information, triggering a market reaction. Trading volume activity shows no significant differences for all three dates, implying that investor trading behavior remained relatively stable regardless of the policy changes. Similarly, the bid-ask spread shows no significant differences on September 18 and December 18, but a significant change on November 7 may indicate temporary changes in market liquidity or investor uncertainty.